2020
DOI: 10.3906/tar-1904-10
|View full text |Cite
|
Sign up to set email alerts
|

Macro- and micromineral contents of different quinoa (Chenopodium quinoa Willd.) varieties used as forage by cattle

Abstract: Mineral deficiencies or mineral excess affect livestock production in most regions of the world. For this reason, it is important to know the mineral contents of forages used in animal feeding. Quinoa (Chenopodium quinoa Willd.), which has become a popular grain crop around the world in recent years, is used as forage in animal feeding. This study was carried out to determine the contents of macro-and microminerals and mineral balance in 9 different quinoa varieties. The results of the study indicated that min… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 16 publications
(20 reference statements)
2
12
0
3
Order By: Relevance
“…The previous study findings that K content varied between 2.9 and 3.3% (Kaya and Aydemir, 2020) and 1.5 and 2.3% (Tan, 2020). It was observed that the present study findings were consistent with previous studies and reported ideal K levels.…”
Section: Calcium (%) and Potassium (%)supporting
confidence: 92%
See 3 more Smart Citations
“…The previous study findings that K content varied between 2.9 and 3.3% (Kaya and Aydemir, 2020) and 1.5 and 2.3% (Tan, 2020). It was observed that the present study findings were consistent with previous studies and reported ideal K levels.…”
Section: Calcium (%) and Potassium (%)supporting
confidence: 92%
“…Phosphorus content reported in previous studies varied between 0.27 and 0.42 % (Kaya and Aydemir, 2020), 0.7, and 1.8 % (Tan, 2020) in different quinoa varieties. In the present study, the P content was low since we harvested the crops after physiological maturity and analyzed the residue plant sections after deseeding.…”
Section: Magnesium (%) and Phosphorus (%)mentioning
confidence: 76%
See 2 more Smart Citations
“…Mn (manganese) from 14.25 to 45.64 mg kg -1 , Mg (magnesium) from 1713 to 3068 mg kg -1 , Fe (iron) from 65.58 to 530 mg kg -1 , Cu (copper) from 5 to 7 mg kg -1 , Zn (zinc) ranged from 1.27 to 14.28 mg kg -1 (Table 8). Tan (2019) reported that Mn from 49.0 to 161.3 mg kg -1 , Mg from 962 to 2344 mg kg -1 , Fe from 265.9 to 498.6 mg kg -1 , Cu from 27.4 to 92.5 mg kg -1 , Zn from 41.3 to 85.2 mg kg -1 ranged. The mineral content of quinoa was collected in the outer bran layer, such as cereals (Repo Carrasco Valencia et al, 2011).…”
Section: Content Of Mineral Mattermentioning
confidence: 99%